Management of liver metastases from non-functional gastroenteropancreatic neuroendocrine tumors: a systematic review - Xue, Jun-shuai; Yang, Yi; Huang, Zhen; Zhao, Hong; Chen, Xiao; Cai, Jian-qiang (Frontiers in Endocrinology, 2025)
The liver is the most common metastatic organ of neuroendocrine tumors (NETs). NET liver metastases (NETLMs) are categorized into simple liver metastasis (type I), complex liver metastasis (type II) and diffuse liver metastasis (type III), of which diffuse liver metastasis accounts for the highest percentage, up to 60-70%. Radical resection is recommended for all patients with type I and partial type II liver metastases without extrahepatic metastases in G1 and G2 grades, with a 5-year survival rate of 65%-70%. But for patients with G3 or type III liver metastases, treatment is controversial. Ablation and TAE/TACE are commonly used localized treatments. Somatostatin analogue (octreotide and lanreotide) are efficacious in the treatment of better-differentiated NETs and can prolong the progression-free survival (PFS) of patients. Targeted drugs such as sunitinib, everolimus, sofantinib and cabozantinib are used to control tumor growth and improve symptoms. In addition, peptide receptor radionuclide therapy (PRRT), has been approved by the FDA for the treatment of progressive somatostatin receptor-positive gastroenteropancreatic NETs and has shown potential for prolonging PFS and improving survival. Multidisciplinary treatment is crucial for patients with NETLMs with high tumor load, and neoadjuvant therapy combined with surgery may lead to a better prognosis. However, the choice of treatment, indications for combination therapy, and disease prognosis still require further research and exploration. This review summarizes and evaluates the current treatment strategies and development trend of NETLM treatment through a literature review and provides new ideas as well as insights.